The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1038/leu.2015.229
|View full text |Cite
|
Sign up to set email alerts
|

Blocking the ZZ domain of sequestosome1/p62 suppresses myeloma growth and osteoclast formation in vitro and induces dramatic bone formation in myeloma-bearing bones in vivo

Abstract: We reported that p62 (sequestosome 1) serves as a signaling hub in bone marrow stromal cells (BMSC) for the formation of signaling complexes, including NFκB, p38MAPK, and JNK, that are involved in the increased osteoclastogenesis and multiple myeloma (MM) cell growth induced by BMSC that are key contributors to myeloma bone disease (MMBD), and demonstrated that the ZZ-domain of p62 (p62-ZZ) is required for BMSC enhancement of MMBD. We recently identified a novel p62-ZZ inhibitor, XRK3F2, that inhibits MM cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 31 publications
(48 reference statements)
3
50
1
Order By: Relevance
“…These cells showed a reduced proliferative capacity and an increase in apoptosis when they lost regulation of RIP1. They are supported by prior studies from Teramachi's laboratory who also observed that cell growth was inhibited by using the inhibitor XRK3F2 that specifically blocks the ZZ domain of p62 in myeloma cells . These results confirm our hypothesis that p62 can regulate the NF‐κB signaling pathway through the ubiquitination of RIP1 in ovarian cancer cells.…”
Section: Discussionsupporting
confidence: 89%
“…These cells showed a reduced proliferative capacity and an increase in apoptosis when they lost regulation of RIP1. They are supported by prior studies from Teramachi's laboratory who also observed that cell growth was inhibited by using the inhibitor XRK3F2 that specifically blocks the ZZ domain of p62 in myeloma cells . These results confirm our hypothesis that p62 can regulate the NF‐κB signaling pathway through the ubiquitination of RIP1 in ovarian cancer cells.…”
Section: Discussionsupporting
confidence: 89%
“…In a subsequent study, a novel small molecule inhibitor of signaling via the ZZ domain of p62 (Sequestosome 1), XRK3F2, blocked tumor necrosis factor (TNF) and multiple myeloma‐induced Gfi1 upregulation, resulting in decreased binding and recruitment of HDAC1 to the RUNX2 promoter in pre‐OBs . These results complement previous in vivo observations in the intratibial‐injected 5TGM1 MM‐KaLwRij syngeneic murine model of MMBD, in which XRK3F2 induced new cortical bone formation in MM‐injected limbs . Collectively, these data argue for the importance of the p62‐ZZ‐domain‐Gfi1 axis in converging the extracellular myeloma signals to HDAC1/EZH2‐mediated epigenetic gene silencing in MM‐BMSC.…”
Section: Chromatin Alterations In Mm‐exposed Bmscssupporting
confidence: 81%
“…Authenticated OPM2, MM1.S and JJN3 cell lines were provided by Dr. G. David Roodman (18) in 2014(IUSM, Indianapolis, IN). BM aspirates of myeloma patients were kindly provided by Dr. Rebecca Silbermann (IUSM, Indianapolis, IN).…”
Section: Methodsmentioning
confidence: 99%